Efek Tonikum Ekstrak Etanol Daun Randu (Ceriba Pentandra (L.) Gaertn) Terhadap Mencit Jantan Galur Swiss Dengan Metode Natatory Exhaustion - Karol Giovani Battista Leki, Karol; Permatasari, Desi (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2023)
Randu leaves are used traditionally to relieve fatigue and increase stamina. This study aims to determine the tonic effect of ethanol extract of randu leaves on male Swiss strain white mice. Tonic effect research was carried out using the Natatory Exhaustion method. This study used 5 test groups, namely negative control (CMC Na 0.5%), positive control (caffeine 100 mg/kgBW), ethanol extract of randu leaves with various doses of 500 mg/kgBW, 1000 mg/kgBW and 2000 mg/kgBW. The research results were analyzed using One Way Anova. The results showed that the ethanol extract of randu leaves had a tonic effect on male white mice.